2011
DOI: 10.1080/21573727.2010.549612
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘one size fits all’: how local conditions shape PPP-enabling field development

Abstract: The use of public-private partnerships (PPPs) for infrastructure development has received significant scholarly attention of late, but there remains a need for more work at the programme level. Specifically, there is a need for work that recognizes the way that PPP programmes are implemented differently in different regions, thereby progressing beyond an effectively 'one size fits all' view of PPP programmes. In response, this paper offers a comparative analysis of the historical development trajectories of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 46 publications
7
52
0
Order By: Relevance
“…Mahalingam, Devkar, and Kalidindi (2011; see also Matos-Castañ o et al, 2014) developed a framework in which they categorise PPP-enabling institutions into mechanisms that facilitate legitimacy, trust and capacity, and link this with earlier academic work (see e.g. Delhi et al, 2010;Jooste et al, 2011). In their view, legitimacy is fostered by a supportive political environment and clear policies, as well as transparent procurement procedures, whereas trust between public and private actors is fostered by means of clear regulations, standards, clear roles of public actors and ex ante evaluation.…”
Section: National Ppp Context: An Institutional Perspectivementioning
confidence: 97%
See 3 more Smart Citations
“…Mahalingam, Devkar, and Kalidindi (2011; see also Matos-Castañ o et al, 2014) developed a framework in which they categorise PPP-enabling institutions into mechanisms that facilitate legitimacy, trust and capacity, and link this with earlier academic work (see e.g. Delhi et al, 2010;Jooste et al, 2011). In their view, legitimacy is fostered by a supportive political environment and clear policies, as well as transparent procurement procedures, whereas trust between public and private actors is fostered by means of clear regulations, standards, clear roles of public actors and ex ante evaluation.…”
Section: National Ppp Context: An Institutional Perspectivementioning
confidence: 97%
“…However, as argued in the literature (e.g. Jooste et al, 2011), countries differ considerably regarding the extent to which they provide governmental support for PPPs in terms of policies and political support, legal frameworks and supporting arrangements.…”
Section: National Ppp Context: An Institutional Perspectivementioning
confidence: 98%
See 2 more Smart Citations
“…However, if we accept the significance of historical and contextual factors for PPPs [23,24], we must also be open to the idea that PPPs in other countries may have an origin and a context more in tune with the efficiency rationale than in the UK. Indeed, Chan and Cheung [25] found that when asked about the reasons for implementing PPP projects, Hong Kong and Australian practitioners rated issues related to improving the overall performance of public projects highly, whereas British practitioners rated financial elements, such as shortage of government funding and avoiding public investment restriction, highly.…”
Section: Financial and Fiscal Motivation For Pppsmentioning
confidence: 99%